Difference Ability Think Critical Using Learning Models Discovery Learning with Problem-Based Learning - Eka Stya Wardani; Hety Mustika Ani; Oktavisanti Mardiyana, Lisana (Basic and Applied Education Research Journal, 2024)
The low ability to think critically students results Study students who don't meet the minimum completeness criteria. This matter is caused by insufficient selection of learning models so that students have difficulty in studying. Study this aims to know the difference in ability to think critically by using the Discovery Learning model and the Problem-based learning model (case study on basics of marketing subject for class X Marketing at SMKN 1 Jember). Study this uses all overpopulation class X PM. The sample is a selection process using a purposive sampling technique. The research methods used​ are quantitative with an experimental design. The technique used for collecting capability data is critical is a test. Research results show that data analysis using the Independent Sample t-test with a level significance of 0.05 results calculations obtained​ is 0.000 < 0.05 which means there is a significant influence.​ From the results, be concluded that there is a considerable difference​ in ability to think critically between class experiments using Problem-Based Learning and classroom learning models controlled using the Discovery Learning model.